Tahapan Kebersyukuran pada Keluarga yang Merawat Penyandang Tunagrahita - Darman, Suwarti; Anggraieni, Livia; Septiningsih, Dyah Siti; Hamzah, Imam Faisal (SAFE-Network, 2024)
People with mental retardation have attachment and dependence on family, and have similarities with normal people. Gratitude is a general tendency to recognize and respond with positive emotions, be grateful for the kindness of others in positive experiences and with what the individual has obtained. The purpose of this study was to examine gratitude in people who care for mentally retarded people (more than one in one house) seen from the stages of gratitude. Data collection used a qualitative interview method with a case study design. Research on 2 primary participants (SR, MT) and 2 secondary participants (TR, SM). Using source triangulation credibility. The results of this study were that both participants experienced gratitude. At the acknowledging stage, 4 themes were found, both participants accepted the shortcomings experienced by their children, participant SR provided supervision and guidance. While participant MT taught her child to do daily activities such as bathing and cleaning the environment. At the recognizing stage, 1 theme was found, both participants were grateful for their treatment which had a good impact. Participant SR succeeded in providing religious education to her grandchildren, while participant MT succeeded in getting her child to do her own routine with her supervision. The two stages experienced by participants make participants have good emotional management.